Formation Of Patient Communication Skills And Expressive Abilities In Future Doctors - et. al., Masuda Kamilzhanovna Khashimova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article discusses the issue of communication of medical personnel with patients, analyzes the specifics and types of communication, the significance, as well as taking into account age characteristics during communication, problems arising from non-compliance with the rules of communication, as well as issues of expressiveness in communication.